Comparison of the UK citizens' perspectives on the consequences of different Brexit scenarios for healthcare: An experimental study. Issue 4 (December 2018) - Esmaeilzadeh, Pouyan; Mirzaei, Tala
Highlights: Leaving the EU may have substantial effects on the UK healthcare. This study uses an experimental approach to collect data from the UK citizens on Brexit roadmap. The public perceptions on medical products, information management, service delivery, and leadership are significantly different between a hard and soft Brexit. This work demonstrates the implications of different Brexit options for the UK healthcare and care services from the British public. The crucial issues and their consequences for health can be addressed in the Brexit negotiations. Abstract: Background: Today, there is a clear understanding of what Brexit means in legal terms and how it involves the health-related issues but, there is no clear view as to how these issues can vary for different Brexit scenarios or how Brexit negotiations impact the citizens healthcare concerns. Objective: In this study, we investigate the facts and issues surrounding Brexit options and their possible influences on healthcare issues from the public perspectives. Methods: We designed two scenarios for controlled online experiments. We used Analysis of Variance to compare participants' perceptions about the two Brexit scenarios (hard and soft). Data were collected from four countries (England, Scotland, Wales and Northern Ireland). Totally, 459 respondents participated in the two experiments. Results: The findings show that there are significance differences in respondents' perceptions of medical products and technologies, information management, service delivery, and healthcare leadership between two Brexit scenarios. Our results show that perception of health risks is significantly lower for soft Brexit scenario comparing to the hard Brexit. Soft Brexit perceived to be significantly more effective in improving medical technology accessibility, information management, service delivery, and healthcare leadership. Conclusions: This work is among the first attempts to describe the way the British public feel about the possible Brexit options' implications for healthcare. The significant difference between Brexit scenarios on medical products, information management, service delivery, and healthcare leadership indicates that the future EU–UK relations depend on how effectively the entire health community and policy systems in the UK address these challenges. The results of this study recommend guidelines for reshaping existing agreements or reaching new arrangements in the Brexit negotiations.